2017
DOI: 10.1007/s00280-017-3453-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-related sinusoidal obstruction syndrome in children with de novo acute lymphoblastic leukemia during intensification

Abstract: SOS following short courses of 6-TG in DI is clinically distinct from SOS following prolonged courses of 6-TG in maintenance, particularly in its early presentation and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…Clinical and laboratory remission were obtained in all six patients. In another study of treatment of acute lymphoblastic leukemia with a brief course of 6thioguanine, 35 The AE profile observed in the present cohort was consistent with that seen in the VOD/SOS population in the post-HSCT setting, and with the known safety profile of defibrotide in such patients. 20,23,25 In the T-IND overall, defibrotide tolerability was better than in other VOD/SOS patient populations, 24,25 prophylaxis study, 26 hemorrhage was the most commonly reported treatment-related AE; however, cumulative hemorrhage incidence was the same between the defibrotide group (22%) and the control group (21%).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Clinical and laboratory remission were obtained in all six patients. In another study of treatment of acute lymphoblastic leukemia with a brief course of 6thioguanine, 35 The AE profile observed in the present cohort was consistent with that seen in the VOD/SOS population in the post-HSCT setting, and with the known safety profile of defibrotide in such patients. 20,23,25 In the T-IND overall, defibrotide tolerability was better than in other VOD/SOS patient populations, 24,25 prophylaxis study, 26 hemorrhage was the most commonly reported treatment-related AE; however, cumulative hemorrhage incidence was the same between the defibrotide group (22%) and the control group (21%).…”
Section: Discussionsupporting
confidence: 85%
“…Clinical and laboratory remission were obtained in all six patients. In another study of treatment of acute lymphoblastic leukemia with a brief course of 6‐thioguanine, 10/680 (1.5%) children developed VOD/SOS; none of the patients were treated with defibrotide. Eight patients with moderate disease made a full recovery; two patients with severe disease died during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In children with haematopoietic malignancies, receiving conventional chemotherapy, SOS was most often observed as the complication of oral 6-thioguanine (6-TG) during maintenance therapy in ALL. SOS following short (14-days) courses of thioguanine is an extremely rare, clinically different, and poorly understood syndrome [7]. Here, we report an uncommon case of sinusoidal obstruction syndrome in a paediatric patient with ALL shortly after completing block of reinduction therapy according to the ALL Intercontinental Berlin-Frankfurt-Münster 2009 (ALL IC BFM 2009) treatment protocol.…”
Section: Introductionmentioning
confidence: 99%
“…They will require blood product transfusions which, at their turn, will generate other possible complications (allergic reactions, infections) [11][12][13][14].…”
Section: Resultsmentioning
confidence: 99%
“…Medullary aplasia represents the most dangerous picture which may occur after chemotherapy and its seriousness is given by the possibility for an infectious clinical picture to occur, which may lead to septicemia, to a hemorrhagic syndrome or to mucosal lesions associated with hemorrhage and necrosis [7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Resultsmentioning
confidence: 99%